2010
DOI: 10.2308/jis.2010.24.2.147
|View full text |Cite
|
Sign up to set email alerts
|

IT and the Board of Directors: An Empirical Investigation into the “Governance Questions” Canadian Board Members Ask about IT

Abstract: In modern organizations, information technologies (IT) often help drive organizational strategies. As such, IT require both judicious planning and oversight. While executive oversight over IT is quite common nowadays, several studies indicate that due to the many benefits and risks associated with IT, more/better board-level oversight may be in order. Unfortunately, there is a scarcity of research on the involvement of board members in IT governance. We attempt to partially fill this gap by empirically examini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Prior studies report that top management's involvement contributes significantly to business-IT alignment (Weill and Ross 2004;Van Grembergen et al 2004;Bart and Turel 2010), higher levels of IT use (Boynton et al 1994), business process performance (Tu et al 2006), and corporate performance (Chen et al 2010). This study used validated firm efficiency and firm strategic growth constructs as proxies for corporate performance (Table 5).…”
Section: Empirical Evidence: Acap-itg-corporate Performancementioning
confidence: 98%
See 2 more Smart Citations
“…Prior studies report that top management's involvement contributes significantly to business-IT alignment (Weill and Ross 2004;Van Grembergen et al 2004;Bart and Turel 2010), higher levels of IT use (Boynton et al 1994), business process performance (Tu et al 2006), and corporate performance (Chen et al 2010). This study used validated firm efficiency and firm strategic growth constructs as proxies for corporate performance (Table 5).…”
Section: Empirical Evidence: Acap-itg-corporate Performancementioning
confidence: 98%
“…Furthermore, Ray et al (2005) revealed that the performance effect of IT is likely to be contingent on the shared knowledge held by IT management. A more recent study by Bart and Turel (2010), using the board members of 94 Canadian firms, reported low usage by the board members of the 27 IT governance points recommended by the Canadian Institute of Chartered Accountants. The authors concluded that the result may be due to the board members' lack of knowledge of IT governance (Bart and Turel 2010).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite acknowledging the importance of board involvement in IT governance, Nolan & McFarlan [10] state that boards are often not aware of the importance of IT when it comes to supporting corporate objectives and the need for alignment between the overall corporate strategy and the IT strategy. Additionally, the board is often incapable to ask IT management "the right questions" due to a lack of expertise, leading to the inability to effectively monitor the management of IT [23]. Strategic alignment is also often perceived as a very complex challenge, to the point where decision makers are unsure about how to approach the alignment challenge [24].…”
Section: It Strategic Alignmentmentioning
confidence: 99%
“…'IT expert on the board', 'IT expert with experience on the board', 'CIO or equivalent is on the board', 'IT committee' etc.). Academic literature indicates that a high degree of board involvement in IT governance, and IT experience at the board, has a positive effect on organizational performance [10], [22], [23]. Despite acknowledging the importance of board involvement in IT governance, Nolan & McFarlan [10] state that boards are often not aware of the importance of IT when it comes to supporting corporate objectives and the need for alignment between the overall corporate strategy and the IT strategy.…”
Section: It Strategic Alignmentmentioning
confidence: 99%